On the other end of research: exploring community-level knowledge exchanges in small-scale fisheries in Zanzibar - Viola Hakkarainen; Tim M. Daw; Maria Tengö (Sustainability Science, 2020)
Sustainability science has increasingly adopted more action-oriented approaches in an attempt to mobilise and implement a broad knowledge base to sustain human wellbeing and promote sustainable development. There is an increasing recognition of the importance of knowledge exchange (KE) between scientists and end users of research for enhancing social, environmental and economic impacts of research. Here, we explore the process of KE through close observation of two cases of KE between external PhD researchers and local actors in small-scale fisheries at the community level in Zanzibar, Tanzania. First, we address context by examining perceptions of research held by actors at community level and patterns of interactions and flows of benefits between external researchers and local actors including fisheries managers, local research institute as well as fishers and traders. Second, we unpack experiences of actors engaged in the cases of KE. The study draws attention to KE processes in the Global South and actors outside decision-making processes in fisheries management. The study concludes that as KE is a complex and dynamic process and that (i) history and relationships between actors shape the outcomes of KE, (ii) KE includes more than knowledge-based processes and outcomes because multiple incentives of different actors shape KE and how it is experiences and (iii) knowledge-based outcomes of KE are complex and unpredictable as different actors create their own meaning from shared information. The results exemplify the inevitably complex and unpredictable nature of KE processes and their outcomes, and provide insight into how KE can contribute to science–society relationships.